Genetic diversity and species pattern of Trichoderma and Hypocrea in Manipur using in silico analysis - Kamala, Thongram (Biomedical Informatics, 2013)
We investigated the occurrence and genetic diversity of Trichoderma and Hypocrea in Manipur which lies in the Indo-Burma biodiversity hot spot region. 65 Trichoderma isolates were identified at species level by morphological as well as sequence based analysis of the internal transcribed spacer region 1 and 4. Altogether 22 different species of Trichoderma and Hypocrea were found, of which Trichoderma harzianum represent the dominant species. Phylogenetic analysis reveals a clear cut distinction of strains isolated from various collection sites which further hints the need for detail study of Trichoderma on molecular level.